Current insights and advances into plant male sterility: new precision breeding technology based on genome editing applications - Farinati, Silvia; Draga, Samela; Betto, Angelo; Palumbo, Fabio; Vannozzi, Alessandro; Lucchin, Margherita; Barcaccia, Gianni (Frontiers in Plant Science, 2023)
Plant male sterility (MS) represents the inability of the plant to generate functional anthers, pollen, or male gametes. Developing MS lines represents one of the most important challenges in plant breeding programs, since the establishment of MS varieties is a major goal in F1 hybrid production. For these reasons, MS varieties have been developed in several species of economic interest, particularly in horticultural crops and ornamental plants. Over the years, MS has been accomplished through many different techniques ranging from approaches based on cross-mediated conventional breeding methods, to advanced devices based on knowledge of genetics and genomics to the most advanced molecular technologies based on genome editing (GE). GE methods, in particular gene knockout mediated by CRISPR/Cas-related tools, have resulted in flexible and successful strategic ideas used to alter the function of key genes, regulating numerous biological processes including MS. These precision breeding technologies result in less time-consuming and can accelerate the creation of new genetic variability with the accumulation of favourable alleles, able to dramatically change the biological process and resulting in a potential efficiency of cultivar development bypassing sexual crosses. The main goal of this manuscript is to provide a general overview of insights and advances into plant male sterility, focusing the attention on the recent new breeding GE-based applications capable of inducing MS by targeting specific nuclear genic loci. A summary of the mechanisms underlying the recent CRISPR technology and relative success applications are described for the main crop and ornamental species. The future challenges and new potential applications of CRISPR/Cas systems in MS mutant production and other potential opportunities will be discussed, as generating CRISPR-edited DNA-free by transient transformation system and transgenerational gene editing for introducing desirable alleles and for precision breeding strategies.